STRUCTURE AND COMPONENTS OF THE DEVELOPMENT OF KNOWLEDGE OF THE CONCEPTS OF CRIME AND PUNISHMENT IN STUDENTS (Scientific journal of the Fergana State University, 2023)
In this article, the protection of the rights and freedoms of citizens is a priority task of every democratic state, and the prevention and fight against crimes committed by students is one of the most urgent issues in the world today. In this regard, opinions on the development of educational, legal consciousness, legal knowledge and legal culture of young people have been presented.